CORPORATE SOCIAL RESPONSIBILITY INITIATIVES OF TOBACCO AND LIQUOR COMPANY IN INDIA: AN EMPIRICAL STUDY - C.P, Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This empirical study explores the Corporate Social Responsibility (CSR) initiatives undertaken by tobacco and liquor companies in India, analysing their strategies, areas of focus, and societal impact. Despite the controversial nature of these industries, many firms actively engage in CSR activities, often in education, health, rural development, and environmental sustainability. Using data collected from respondents, annual reports, CSR disclosures, and interviews with key stakeholders, this study assesses whether these initiatives are genuine attempts at social contribution or strategic efforts to enhance corporate image and mitigate regulatory scrutiny. The findings suggest a complex interplay between regulatory compliance, brand positioning, and ethical considerations. While some CSR activities create tangible social benefits, questions persist regarding their alignment with the core business impact on public health. The study offers policy recommendations and calls for more stringent evaluation mechanisms to ensure authenticity and accountability in CSR practices of these sectors.